Diseño de procedimientos para un operador logístico para la distribución y reparto para una compañía de correos - Johnny, Real Roby (2010)
The present article refers to the design of procedures for a logistic operator for the distribution and the delivery for a post office company. At the first time the present situation of the company is analyzed, by means of tables about the vehicles information, amount of shipments that are distributed daily and route diagrams, specifying each one of the areas involved in the process of distribution with its respective stages by type of service. Then, the exposition of measurement indicators is made for being able to compare the present situation with the future, one after the implementation of the propose improvements as the design of policies and procedures for the main operative processes of the company and the application of method SLP (Systematic Layout Planning) for the relocation of the operations in the study processes optimizing resources and installed capacity. Additionally, the use of a transporting bands system is made to increase the speed of production of the Classification National Center. Finally the Cost-Benefit analysis from the project is made for obtaining as a result that the project has a very good economic viability and a turnaround time of investment in a short term.